A small loss for an expanding city: Vakko textile factory. Issue 3 (2nd September 2019) - Özdamar, Esen Gökçe
ABSTRACT: This article focuses on the Vakko textile factory, a modernist industrial building on the E-5 highway in İstanbul Merter, built in 1969 and demolished in 2006. As one of the pioneering locations for modern fashion in Turkey, this factory is among the increasing number of modernist heritage buildings that has been lost due to demolition in the sprawling city of İstanbul. However, the building was demolished because of urban policies as well as company decisions. With its microenvironment and landscaping, this industrial concrete building has witnessed changes in Turkey's social, economic, and political context from the Hat Law of 1925 to ready-to-wear production starting in the 1970s. The building can be considered one of the most important and the most beautiful examples of modern industrial architecture and international style in Turkey, embracing plastic arts and graphic arts in a period of industrialization as stated by Cengizkan and Kaçel. The building is not only a modernist concrete structure, but also displays the socio-political, economic, and artistic approaches of the period and Turkish postwar modernism. However, this 'small-scale loss' building with its conserved and restored unique art works becomes one of the few examples in İstanbul as an expanding city.